Glass composition for glass fiber, glass fiber, glass fiber fabric and glass fiber reinforced resin composition

By adjusting the chemical composition of glass fibers, especially the ratio of Nb2O5 and SO3, the problems of bubble residues and dielectric loss in glass fiber manufacturing are solved, and the production of glass fibers with low dielectric constant and low dielectric loss tangent is achieved. The defoaming process time is shortened, and manufacturing efficiency and energy utilization are improved.

CN118715187BActive Publication Date: 2025-01-17NITTO BOSEKI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380022258.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-06-05
Publication Date
2025-01-17
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

Existing glass fibers are prone to residual bubbles during the manufacturing process, resulting in fracture and reduced reliability. Glass fibers with low dielectric constant and low dielectric loss tangent need a long time in the defoaming process, increasing energy consumption and cost.

Method used

The ratio of SO3/Nb2O5 is controlled by adjusting the ratio of SiO2, B2O3, Al2O3, MgO, CaO, SrO, TiO2, F2 and Cl2 is used to control the ratio of SO3/Nb2O5 by adjusting the ratio of SiO2, B2O3, Al2O3, MgO, CaO, SrO, TiO2, F2 and Cl2. In the range of 0.07 to 13.70, glass fibers with low dielectric constant and low dielectric loss tangent are formed, and the defoaming process time is shortened.

Benefits of technology

It effectively suppresses the infiltration of bubbles, reduces dielectric loss, shortens the defoaming process time, improves the quality and manufacturing efficiency of glass fibers, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a glass composition for glass fiber capable of obtaining glass fiber having a low dielectric constant and a low dielectric loss tangent and capable of shortening a degassing process. The glass composition for glass fiber of the present invention contains Nb2O5 in the range of 0.0001 to 0.3500 mass % and SO3 in the range of 0.0010 to 0.0100 mass % relative to the total amount. When the remainder after removing SO3 and Nb2O5 from the above total amount is set to 100 mass parts, the glass composition for glass fiber contains 48.0 to 60.0 mass parts of SiO2, 18.4 to 27.0 mass parts of B2O3, 10.8 to 17.0 mass parts of Al2O3, 0 to 2.5 mass parts of MgO, 0 to 6.0 mass parts of CaO, 0 to 4.5 mass parts of SrO, 0.5 to 3.5 mass parts of TiO2 and a total of 0 to 2.5 mass parts of F2 and Cl2, and the content ratio SO3 / Nb2O5 is in the range of 0.07 to 13.70.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a glass composition for glass fiber, glass fiber, glass fiber fabric and glass fiber reinforced resin composition. Background Art

[0002] Conventionally, glass fiber has been widely used in various applications to improve the strength of resin molded products, which are used in parts such as housings and printed wiring boards of electronic devices such as servers, smartphones, and notebook computers.

[0003] Generally, glass absorbs energy from an alternating current to generate heat. Therefore, when the resin molded article is used for a housing or an accessory of the electronic device, there is a problem that the resin molded article generates heat.

[0004] Here, the dielectric loss absorbed by glass as heat among the transmission losses representing attenuation of communication signals is proportional to the square root of the dielectric constant and the dielectric loss tangent determined by the composition and structure of the glass, and is represented by the following formula (A).

[0005] W=kf×ε 1 / 2 ×tanδ…(A)

[0006] Here, W represents dielectric loss, k represents constant, f represents frequency, ε represents dielectric constant, and tanδ represents dielectric loss tangent. As can be seen from formula (A), the greater the dielectric constant and dielectric loss tangent, and the higher the frequency, the greater the dielectric loss, and the greater the heat generated by the resin molded product.

[0007] In recent years, due to the increase in the frequency of the alternating current used in the above-mentioned electronic devices (f in the above formula (A)), in order to reduce dielectric loss, the glass fiber used in the housing or components of the above-mentioned electronic devices is required to have a lower dielectric constant and a lower dielectric loss tangent.

[0008] As the glass fiber having a low dielectric constant and a low dielectric loss tangent, the present applicant has proposed the following glass composition for glass fiber (see Patent Document 1): the glass composition contains SiO in a range of 52.0 to 59.5 mass % relative to the total amount of the glass fiber. 2 , 17.5 to 25.5 mass % B 2 O 3 , 9.0 to 14.0 mass % of Al 2 O 3 , 0.5 to 6.0 mass % SrO, 1.0 to 5.0 mass % MgO, 1.0 to 5.0 mass % CaO, and 0.1 to 2.5 mass % F in total 2 and Cl 2 .

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent No. 6468409 Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, when glass fibers are used for printed wiring boards, etc., if bubbles remain in the glass fibers, the glass fibers may break during spinning or their reliability may be significantly reduced when they are made into printed wiring boards. Therefore, it is required to suppress the mixing of bubbles into the glass fibers.

[0014] Generally, when manufacturing glass fibers without residual bubbles, when using E-glass fibers having the most common glass composition, the bubbles in the molten glass are removed by melting the E-glass fibers at a melting temperature higher than the spinning temperature (e.g., 100 poise temperature), and then spinning is carried out at a spinning temperature (1000 poise temperature), thereby obtaining glass fibers with zero bubbles.

[0015] However, when manufacturing the glass fiber having a low dielectric constant and a low dielectric loss tangent as described in Patent Document 1, unlike the case of the above-mentioned E glass fiber, even if the number of bubbles and the volume of bubbles in the molten glass are sufficiently reduced by using a temperature higher than the spinning temperature, new bubbles will be generated when the temperature of the molten glass is cooled to the spinning temperature. Therefore, there is a problem of needing to further perform a melting process for a long time after the temperature of the molten glass is lowered to near the spinning temperature (hereinafter sometimes referred to as a degassing process).

[0016] In order to ensure a long time for the above-mentioned degassing process, it is necessary to increase the volume of the melting tank where the molten glass used in the degassing process is retained, thereby unnecessarily increasing the size of the melting tank (melting furnace). As a result, the power required for melting increases, and more furnace materials need to be used, which is not economical.

[0017] An object of the present invention is to provide a glass composition for glass fibers which can obtain glass fibers having a low dielectric constant and a low dielectric loss tangent and can shorten the time required for a degassing step by eliminating the above-mentioned disadvantages.

[0018] In addition, the present invention also provides glass fibers containing glass filaments formed from the glass composition for glass fibers, glass fiber fabrics containing the glass fibers, and glass fiber-reinforced resin compositions containing the glass fibers.

[0019] Means for solving problems

[0020] In order to achieve the above object, the glass composition for glass fiber of the present invention is characterized in that it contains Nb in a range of 0.0001 to 0.3500 mass % based on the total amount of the glass composition for glass fiber. 2 O 5 and SO in the range of 0.0010 to 0.0100 mass % 3 , SO will be removed from the total amount of glass composition used for glass fiber 3 and Nb 2 O 5 When the remainder after the addition is set to 100 parts by mass, the glass composition for glass fiber contains 48.0 to 60.0 parts by mass of SiO 2 , 18.4 to 27.0 parts by mass of B 2 O 3 , 10.8 to 17.0 parts by mass of Al 2 O 3 , MgO in the range of 0 to 2.5 parts by mass, CaO in the range of 0 to 6.0 parts by mass, SrO in the range of 0 to 4.5 parts by mass, TiO in the range of 0.5 to 3.5 parts by mass 2 and a total of 0 to 2.5 parts by mass of F 2 and Cl 2 , SO 3 The content relative to Nb 2 O 5 The content ratio (SO 3 / Nb 2 O 5 ) values ​​range from 0.07 to 13.70.

[0021] According to the glass composition for glass fibers of the present invention, by having the above-mentioned composition, glass fibers having a low dielectric constant and a low dielectric loss tangent can be obtained, and even if the time required for the degassing step is shortened, mixing of bubbles into the glass fibers can be suppressed.

[0022] It should be noted that, here, the glass fiber obtained from the glass composition for glass fiber of the present invention has a low dielectric constant, which means that the dielectric constant is 4.6 or less at a measurement frequency of 10 GHz, and has a low dielectric loss tangent, which means that the dielectric loss tangent is 0.0024 or less at a measurement frequency of 10 GHz.

[0023] In addition, the glass fiber of the present invention is characterized by comprising glass filaments formed from the glass composition for glass fibers of the present invention, and the glass fiber fabric and glass fiber-reinforced resin composition of the present invention are characterized by comprising the glass fiber of the present invention. DETAILED DESCRIPTION

[0024] Next, embodiments of the present invention will be described in detail.

[0025] The glass composition for glass fiber of the present embodiment contains Nb in an amount ranging from 0.0001 to 0.3500 mass % based on the total amount of the glass composition for glass fiber. 2 O 5 and SO in the range of 0.0010 to 0.0100 mass % 3 , in which SO will be removed from the total amount of glass composition used for glass fiber 3 and Nb 2 O 5 When the remainder after the addition is set to 100 parts by mass, the glass composition for glass fiber contains 48.0 to 60.0 parts by mass of SiO 2 , 18.4 to 27.0 parts by mass of B 2 O 3 , 10.8 to 17.0 parts by mass of Al 2 O 3 , MgO in the range of 0 to 2.5 parts by mass, CaO in the range of 0 to 6.0 parts by mass, SrO in the range of 0 to 4.5 parts by mass, TiO in the range of 0.5 to 3.5 parts by mass 2 and a total of 0 to 2.5 parts by mass of F 2 and Cl 2 , SO 3 The content relative to Nb 2 O 5 The content ratio (SO 3 / Nb 2 O 5 ) values ​​range from 0.07 to 13.70.

[0026] In the glass composition for glass fiber of this embodiment, if Nb 2 O 5 If the content of Nb is less than 0.0001 mass % relative to the total amount of the glass composition used for the glass fiber, the clarification effect during glass melting cannot be well exerted, and it is difficult to reduce the number of bubbles before lowering the temperature of the molten glass. 2 O 5 When the content of the glass composition for glass fiber exceeds 0.3500 mass %, bubbles are excessively generated in the molten glass, so that a longer degassing process is required. Here, the above-mentioned clarifying effect means that the bubbles generated in the vitrification process from the batch material are different from those in Nb 2 O 5 The bubbles generated when melting into glass etc. grow together or are caught in the bubbles and float out of the molten glass, thereby promoting the degassing effect.

[0027] In the glass composition for glass fiber of this embodiment, Nb 2 O 5 The content relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.1000 mass % or less, more preferably in the range of 0.0500 mass % or less, further preferably in the range of 0.0300 mass % or less, particularly preferably in the range of 0.0100 mass % or less, and most preferably in the range of 0.0010 to 0.0050 mass %.

[0028] In the glass composition for glass fiber of this embodiment, if SO 3 If the content of the glass composition for glass fiber is less than 0.0010 mass %, the clarifying effect of glass melting is too small, and a large number of bubbles remain before the temperature of the molten glass is lowered, and it takes a longer time to perform the degassing process, resulting in that the number of bubbles cannot be sufficiently reduced even after the degassing process. 3 When the content exceeds 0.0100 mass % based on the total amount of the glass composition for glass fibers, new bubbles are excessively generated during temperature reduction, and a longer time is required for the degassing step.

[0029] In the glass composition for glass fiber of this embodiment, SO 3 The content of the glass composition for glass fibers is preferably in the range of 0.0020 to 0.0080 mass %, more preferably in the range of 0.0035 to 0.0070 mass %, and most preferably in the range of 0.0040 to 0.0050 mass %.

[0030] In addition, in the glass composition for glass fiber of the present embodiment, when SO 3 The content relative to Nb 2 O 5 The content ratio (SO 3 / Nb 2 O 5 ) is less than 0.07, the Nb 2 O 5 The foaming becomes too intense, so the degassing process takes longer. 3 The content relative to Nb 2 O 5 The content ratio (SO 3 / Nb 2 O 5 ) exceeds 13.70, SO cannot be suppressed 3 The molten glass foams when the temperature is lowered, so that the degassing process takes a longer time.

[0031] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount after SiO is set to 100 parts by mass, 2 If the content of SiO is less than 48.0 parts by mass, the mechanical strength of the glass fiber obtained from the glass composition for glass fiber is greatly reduced, and the function of the glass fiber as a reinforcing material in the glass fiber reinforced resin composition is impaired. 2 If the content exceeds 60.0 parts by mass, the viscosity at high temperature becomes high, so the temperature at which the glass raw material melts increases, which is not suitable for industrial glass fiber production from the viewpoint of production cost.

[0032] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount is set to 100 parts by mass, SiO 2 The content of is preferably in the range of 51.1 to 56.9 parts by mass, more preferably in the range of 52.1 to 55.9 parts by mass, further preferably in the range of 52.4 to 55.2 parts by mass, particularly preferably in the range of 52.7 to 54.5 parts by mass, and most preferably in the range of 53.0 to 54.4 parts by mass.

[0033] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount after is set to 100 parts by mass, if B 2 O 3 If the content of B is less than 18.4 mass %, the dielectric loss tangent of the glass fiber obtained from the glass composition for glass fiber cannot be sufficiently reduced. 2 O 3 When the content of exceeds 27.0 mass %, the glass fiber obtained from the glass composition for glass fiber may undergo phase separation, which may result in a decrease in the chemical durability of the glass fiber.

[0034] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount after is set to 100 parts by mass, B 2 O 3The content is preferably in the range of 19.4 to 25.5 mass %, more preferably in the range of 20.1 to 24.9 mass %, further preferably in the range of 20.7 to 24.4 mass %, particularly preferably in the range of 21.6 to 24.2 mass %, particularly preferably in the range of 22.0 to 23.8 mass %, and most preferably in the range of 22.4 to 23.4 mass parts.

[0035] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount after Al is set to 100 parts by mass, 2 O 3 If the content of Al is less than 10.8 parts by mass, the glass fiber obtained from the glass composition for glass fiber will undergo phase separation, which may lead to a decrease in the chemical durability of the glass fiber. 2 O 3 When the content exceeds 17.0 parts by mass, the dielectric loss tangent of the glass fiber obtained from the glass composition for glass fibers cannot be sufficiently reduced.

[0036] In the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount is set to 100 parts by mass, Al 2 O 3 The content of is preferably in the range of 11.7 to 16.4 parts by mass, more preferably in the range of 12.1 to 15.9 parts by mass, further preferably in the range of 12.6 to 15.4 parts by mass, particularly preferably in the range of 12.9 to 14.9% by mass, and most preferably in the range of 13.2 to 14.7 parts by mass.

[0037] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after MgO is set to 100 parts by mass, if the content of MgO exceeds 2.5 parts by mass, striae may be generated in the melt of the glass composition for glass fiber, which may make the glass fiber more likely to break during spinning.

[0038] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5When the remainder after addition is set to 100 parts by mass, the content of MgO is preferably in the range of 0.1 to 2.3 parts by mass, thereby suppressing the crystallization of the glass and suppressing the increase in the liquidus temperature, thereby fully ensuring the operating temperature range. In the glass composition for glass fiber of this embodiment, after removing SO from the total amount, 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the content of MgO is more preferably in the range of 0.2 to 2.0 parts by mass, further preferably in the range of 1.9 parts by mass or less, particularly preferably in the range of 0.3 to 1.2 parts by mass, particularly preferably in the range of 0.5 to 1.1 parts by mass, extremely preferably in the range of 0.5 to 0.9 parts by mass, and most preferably in the range of 0.7 to 0.95 parts by mass.

[0039] In the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after CaO is set to 100 parts by mass, if the content of CaO exceeds 6.0 parts by mass, the dielectric loss tangent of the glass fiber obtained from the glass composition for glass fiber cannot be sufficiently reduced.

[0040] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the content of CaO is preferably in the range of 0.5 to 5.8 parts by mass, thereby suppressing the crystallization of the glass and reducing the resistance value of the molten glass at high temperatures. In the glass composition for glass fiber of the present embodiment, after removing SO from the total amount, 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the CaO content is preferably in the range of 0.5 to 5.8 parts by mass, more preferably in the range of 1.0 to 5.5 parts by mass, further preferably in the range of 2.0 to 5.3 parts by mass, particularly preferably in the range of 2.8 to 5.1 parts by mass, particularly preferably in the range of 3.2 to 4.9 parts by mass, and most preferably in the range of 3.5 to 4.8 parts by mass.

[0041] In the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after SrO is set to 100 parts by mass, if the content of SrO exceeds 4.5 parts by mass, the dielectric properties of glass fibers obtained from the glass composition for glass fibers deteriorate and cannot satisfy the target dielectric properties.

[0042] In the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the content of SrO is preferably in the range of 3.1 parts by mass or less, more preferably in the range of 2.9 parts by mass or less, further preferably in the range of 2.5 parts by mass or less, particularly preferably in the range of 2.3 parts by mass or less, and most preferably in the range of 2.1 parts by mass or less, thereby being able to reduce the dielectric loss tangent of the obtained glass fiber. On the other hand, in the glass composition for glass fiber of the present embodiment, after removing SO from the total amount, 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the content of SrO is preferably in the range of 0.1 parts by mass or more. 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the SrO content is more preferably in the range of 0.5 parts by mass or more, further preferably in the range of 0.8 parts by mass or more, particularly preferably in the range of 1.2 parts by mass or more, and most preferably in the range of 1.5 parts by mass or more, thereby facilitating the long fiberization of the glass fiber.

[0043] In the above-mentioned glass composition for glass fiber, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount after is set to 100 parts by mass, if TiO 2 If the content of TiO is less than 0.5 parts by mass, the viscosity at high temperature becomes high, so the temperature for melting the glass raw material becomes high, which is not suitable for industrial glass fiber production from the perspective of manufacturing cost. 2 If the content exceeds 3.5 parts by mass, the dielectric loss tangent of the glass fiber obtained from the glass composition for glass fiber cannot be sufficiently reduced. In addition, the liquidus temperature of the glass composition for glass fiber increases significantly, so that the glass fiber cannot be stably produced.

[0044] In the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount is set to 100 parts by mass, TiO 2 The content of 0.7 to 3.2 parts by mass is preferably in the range of 0.9 to 2.7 parts by mass, and further preferably in the range of 1.2 to 2.5 parts by mass.

[0045] In the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount after the reaction is set to 100 parts by mass, if F 2 and Cl 2 If the total content of exceeds 2.5 parts by mass, the chemical durability of glass fibers obtained from the glass composition for glass fibers decreases.

[0046] In the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount after is set to 100 parts by mass, F 2 and Cl 2 The total content of SO is preferably 0.1% or more, which can reduce the viscosity at high temperature, improve the dielectric properties of glass, and reduce the dielectric constant and dielectric loss tangent. In the glass composition for glass fiber of this embodiment, after removing SO from the total amount 3 and Nb 2 O 5 When the remaining amount after is set to 100 parts by mass, F 2 and Cl 2 The total content of is preferably in the range of 0.1 to 2.2 mass %, more preferably in the range of 0.3 to 1.9 mass %, further preferably in the range of 0.5 to 1.6 mass %, particularly preferably in the range of 0.6 to 1.4 mass %.

[0047] In the glass composition for glass fiber of the present embodiment, Cl 2 The content of F 2 The content ratio of is preferably in the range of 1.0% or less, more preferably in the range of 0.1% or less, whereby the generation of bubbles in the defoaming step tends to be suppressed, and the time required for the defoaming step tends to be further shortened.

[0048] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remainder after 100 parts by mass is set, the total amount of Na contained in the range of less than 1.00 parts by mass may be 2 O.K 2 O and Li 2 O. The glass composition for glass fiber of this embodiment contains Na 2 O.K 2 O and Li 2O, if the total content thereof exceeds 1.00 parts by mass, the dielectric properties of glass fibers obtained from the glass composition for glass fibers are greatly deteriorated, and the target dielectric properties cannot be achieved.

[0049] will remove SO from the total 3 and Nb 2 O 5 When the balance after 100 parts by mass is set, the glass composition for glass fiber of this embodiment contains Na 2 O.K 2 O and Li 2 In the case of O, Na 2 O.K 2 O and Li 2 The total content of O is preferably less than 0.80 part by mass, more preferably less than 0.50 part by mass, further preferably less than 0.20 part by mass, particularly preferably less than 0.10 part by mass, and most preferably less than 0.05 part by mass.

[0050] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after the addition is set to 100 parts by mass, ZnO in the range of 0 to 3.00 parts by mass may be contained. In the case where the glass composition for glass fiber of the present embodiment contains ZnO, if the content of ZnO exceeds 3.00 parts by mass, the glass fiber obtained from the glass composition for glass fiber is prone to produce devitrified materials during spinning, and the glass fiber cannot be stably manufactured. In addition, the dielectric properties of the glass fiber deteriorate.

[0051] When the glass composition for glass fiber of the present embodiment contains ZnO, SO 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the content of ZnO is preferably in the range of 2.50 parts by mass or less, more preferably in the range of 1.50 parts by mass or less, further preferably in the range of 0.50 parts by mass or less, particularly preferably in the range of 0.10 parts by mass or less, and most preferably in the range of less than 0.01 parts by mass.

[0052] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remainder after the addition is set to 100 parts by mass, less than 4.00 parts by mass of P may be contained. 2 O5 The glass composition for glass fiber of this embodiment contains P 2 O 5 In this case, SO will be removed from the total 3 and Nb 2 O 5 When the remaining amount after is set to 100 parts by mass, if P 2 O 5 When the content is 4.00 parts by mass or more, the phase separation of the glass fiber obtained from the glass composition for glass fiber cannot be suppressed, and the water resistance deteriorates.

[0053] The glass composition for glass fiber of this embodiment contains P 2 O 5 In the case of 3 and Nb 2 O 5 When the remaining amount after is set to 100 parts by mass, P 2 O 5 The content is preferably in the range of 3.0 parts by mass or less, more preferably in the range of 2.50 parts by mass or less, further preferably in the range of 1.50 parts by mass or less, particularly preferably in the range of 0.40 parts by mass or less, particularly preferably in the range of 0.10 parts by mass or less, and most preferably in the range of less than 0.01 parts by mass.

[0054] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after the addition is set to 100 parts by mass, Fe may be contained in the range of 0 to 1.00 parts by mass. 2 O 3 In the glass composition for glass fiber of the present embodiment, in the glass composition containing Fe 2 O 3 In the case of Fe, from the viewpoint of suppressing bubbles contained in the glass fiber, Fe is effective. 2 O 3 The content of is in the range of 0.05 to 0.60 parts by mass.

[0055] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after the addition is set to 100 parts by mass, SnO may be contained in a range of 0 to 1.00 parts by mass. 2 The glass composition for glass fiber of this embodiment contains SnO 2In the case of SnO, from the viewpoint of suppressing bubbles contained in the glass fiber, SnO is effective. 2 The content of is in the range of 0.05 to 0.60 parts by mass.

[0056] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after 100 parts by mass is set, MnO can be contained in the range of 0 to 3.00 parts by mass. 2 The glass composition for glass fiber of this embodiment contains MnO 2 In the case of MnO 2 If the content exceeds 3.00 parts by mass, the dielectric properties of glass fibers obtained from the glass composition for glass fibers deteriorate, and desired dielectric properties cannot be obtained.

[0057] The glass composition for glass fiber of the present embodiment contains MnO 2 In this case, SO will be removed from the total 3 and Nb 2 O 5 When the remaining amount after MnO is set to 100 parts by mass, 2 The content of is preferably in the range of 2.50 parts by mass or less, more preferably in the range of 1.50 parts by mass or less, and still more preferably in the range of 0.50 parts by mass or less.

[0058] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the balance after 100 parts by mass is set, ZrO may be contained in an amount less than 0.60 parts by mass. 2 The glass composition for glass fiber of this embodiment contains ZrO 2 In this case, SO will be removed from the total 3 and Nb 2 O 5 When the remaining amount is set to 100 parts by mass, ZrO 2 The content is preferably in the range of less than 0.60 mass part, more preferably in the range of less than 0.45 mass part, further preferably in the range of less than 0.40 mass part, especially preferably in the range of less than 0.20 mass part, particularly preferably in the range of less than 0.10 mass part, and most preferably in the range of less than 0.05 mass part.

[0059] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb2 O 5 When the balance after Cr is set to 100 parts by mass, Cr in the range of less than 0.05 parts by mass may be contained. 2 O 3 The glass composition for glass fiber of this embodiment contains Cr 2 O 3 In this case, SO will be removed from the total 3 and Nb 2 O 5 When the remaining amount after Cr is set to 100 parts by mass, 2 O 3 If the content is 0.05 parts by mass or more, devitrified matter is likely to be produced during spinning of glass fibers obtained from the glass composition for glass fibers, and thus glass fibers cannot be stably produced.

[0060] In addition, in the glass composition for glass fiber of the present embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remainder after addition is set to 100 parts by mass, the oxide of Ba, Co, Ni, Cu, Mo, W, Ce, Y, La, Bi, Gd, Pr, Sc or Yb may be contained in a total of less than 3.00 parts by mass as impurities derived from the raw materials, and preferably less than 2.00 parts by mass, and more preferably less than 1.00 parts by mass. In particular, the glass composition for glass fiber of the present embodiment contains BaO, CeO 2 , Y 2 O 3 ,La 2 O 3 、Bi 2 O 3 , Gd 2 O 3 , Pr 2 O 3 Sc 2 O 3 or Yb 2 O 3 In the case of impurities, the content of each of them is preferably less than 0.40 parts by mass, more preferably less than 0.20 parts by mass, further preferably less than 0.10 parts by mass, particularly preferably less than 0.05 parts by mass, and most preferably less than 0.01 parts by mass.

[0061] In the glass composition for glass fiber of this embodiment, SO is removed from the total amount. 3 and Nb 2 O 5 When the remaining amount is set to 100 parts by mass, SiO2 , B 2 O 3 、Al 2 O 3 , MgO, CaO, SrO, TiO 2 、F 2 and Cl 2 The total content of is, for example, in the range of 91.0 parts by mass or more, preferably in the range of 95.0 parts by mass or more, more preferably in the range of 98.0 parts by mass or more, further preferably in the range of 99.0 parts by mass or more, particularly preferably in the range of 99.3 parts by mass or more, particularly preferably in the range of 99.5 parts by mass or more, extremely preferably in the range of 99.7 parts by mass or more, and most preferably in the range of 99.9 parts by mass or more.

[0062] It should be noted that regarding the measurement of the content of the above-mentioned components in the glass composition for glass fiber of this embodiment, Li as a light element can be measured using an ICP emission spectrometer, and the content of other elements can be measured using a wavelength dispersive fluorescent X-ray analyzer.

[0063] As a measuring method, the content is described as follows: First, a glass batch (a glass batch prepared by mixing glass raw materials) or glass fiber is placed in a platinum crucible. When a glass batch is used, it is placed in a platinum crucible with a diameter of 80 mm in an electric furnace, and the temperature is raised from room temperature to 1650°C at a heating rate of 10°C / min, and after melting at a temperature of 1650°C for 2 hours, the temperature is lowered to 1450°C at a cooling rate of 10°C / min, and maintained for 10 minutes to obtain a homogeneous molten glass. At this time, in the case where organic matter is attached to the surface of the glass fiber or in the case where the glass fiber is mainly contained as a reinforcing material in the organic matter (resin), for example, the glass fiber is used after heating in a muffle furnace at 300 to 650°C for about 0.5 to 24 hours, etc., and the organic matter is removed.

[0064] Next, the obtained molten glass is poured onto a carbon plate to form glass chips, which are then crushed and powdered to form glass powder. The glass powder is formed into a disk shape using a press, and then Nb and S are measured by the fundamental parameter method using a wavelength dispersive X-ray fluorescence analyzer. For elements other than Nb and S, the content of each component can be analyzed by the method described below. 2 O 5 、SO 3 The content of each component was calculated so that the remainder after addition was assumed to be 100 parts by mass, and the content of each component described above was obtained from these numerical values.

[0065] The analysis of the content of elements other than Nb and S can be carried out in the following manner: after the obtained glass powder is heated and decomposed with acid, Li as a light element is quantitatively analyzed using an ICP emission spectrometer. The glass powder can be formed into a disc shape using a press, and then other elements can be quantitatively analyzed using a wavelength dispersive fluorescence X-ray analyzer. The quantitative analysis using a wavelength dispersive fluorescence X-ray analyzer can be specifically carried out in the following manner: a sample for a standard curve is prepared based on the results measured by the fundamental parameter method, and the sample is analyzed by the standard curve method. It should be noted that the content of each component in the sample for the calibration curve can be quantitatively analyzed by an ICP emission spectrometer.

[0066] The dielectric constant of the glass composition for glass fiber of this embodiment is preferably 4.6 or less at a measurement frequency of 10 GHz, more preferably 4.4 or less. In addition, although the lower limit of the dielectric constant is not particularly limited, it is preferably 3.7 or more.

[0067] In addition, the dielectric loss tangent of the glass composition for glass fiber of the present embodiment is preferably in the range of 0.0024 or less at a measurement frequency of 10 GHz, more preferably in the range of 0.0021 or less, and further preferably in the range of 0.0019 or less. In addition, although the lower limit of the dielectric loss tangent is not particularly limited, the lower limit is preferably in the range of 0.0008 or more.

[0068] The glass composition for glass fibers of the present embodiment can be obtained by melting glass raw materials (glass batch material) prepared so as to have the above-mentioned composition after being melted and solidified, and then cooling and solidifying.

[0069] When the glass composition for glass fiber of the present embodiment is used to form the glass fiber of the present embodiment, first, the glass raw material prepared in the above manner is supplied to a glass melting furnace and melted at a melting temperature region higher than the above spinning temperature, specifically at a temperature in the range of 1510 to 1700°C. Next, the molten glass melted to the above temperature is supplied to a melting tank controlled to a spinning temperature region, specifically at a temperature range of 1300 to 1500°C. Next, a degassing process is performed: that is, the molten glass is retained in the above melting tank for a time range of 5 minutes to 96 hours to eliminate the bubbles contained in the molten glass. The time of the above degassing process is preferably in the range of 5 minutes to less than 30 minutes, and more preferably in the range of 5 minutes to less than 10 minutes. Next, the molten glass is ejected from a nozzle head or hole in the range of 1 to 8000, and is stretched while cooling and solidifying by high-speed winding, thereby forming glass fibers.

[0070] Here, the glass single fiber (glass yarn) ejected from a nozzle head or hole and cooled and solidified usually has a perfect circular cross-sectional shape and a diameter range of 3.0 to 35.0 μm. In applications where low dielectric properties are required, the glass filament preferably has a diameter range of 3.0 to 6.0 μm, and more preferably has a diameter range of 3.0 to 4.5 μm. On the other hand, in the case where the nozzle head has a non-circular shape and has a protrusion or a cutout for quenching the molten glass, by controlling the temperature conditions, a glass filament having a non-circular (e.g., elliptical, oblong) cross-sectional shape can be obtained. In the case where the glass filament has an elliptical or oblong cross-sectional shape, the ratio of the major diameter to the minor diameter of the cross-sectional shape (major diameter / minor diameter) is, for example, in the range of 2.0 to 10.0, and the fiber diameter (converted fiber diameter) when the cross-sectional area is converted into a perfect circle is in the range of 3.0 to 35.0 μm.

[0071] The glass fiber of this embodiment is usually in the shape of a glass fiber bundle (glass strand) formed by bundling the glass filaments in the range of 10 to 8000, and has a weight range of 1 to 10000 tex (g / km). It should be noted that the glass filaments ejected from multiple nozzle heads or holes are sometimes bundled into one glass fiber bundle, and sometimes bundled into multiple glass fiber bundles.

[0072] The glass fiber of the present embodiment can be in various forms such as yarn, woven fabric, knitted fabric, nonwoven fabric (including chopped strand mat and multiaxial nonwoven fabric), chopped strand, roving, powder, etc., which can be obtained by further processing the above-mentioned glass raw yarn in various ways.

[0073] In order to improve the bundling of glass filaments, improve the adhesion of glass fiber to resin, improve the uniform dispersion of glass fiber in a mixture of glass fiber and resin or inorganic material, etc., the glass fiber of the present embodiment can be coated with an organic substance on its surface. As such organic substances, starch, polyurethane resin, epoxy resin, vinyl acetate resin, acrylic resin, modified polypropylene (especially carboxylic acid-modified polypropylene), copolymers of (poly) carboxylic acid (especially maleic acid) and unsaturated monomers, etc. can be cited. In addition, in addition to being coated with the above-mentioned resin, the glass fiber of the present embodiment can also be coated with a resin composition containing a silane coupling agent, a lubricant, a surfactant, etc. In addition, the glass fiber of the present embodiment can also be coated with a treatment agent composition that does not contain the above-mentioned resin but contains a silane coupling agent, a surfactant, etc. Based on the mass of the glass fiber of the present embodiment in a state not coated with a resin composition or a treatment agent composition, such a resin composition or a treatment agent composition coats the glass fiber in a ratio of 0.03 to 2.0 mass %. It should be noted that the coating of glass fiber with organic matter can be carried out, for example, by the following method: in the manufacturing process of glass fiber, a known method such as a roller-type applicator is used to apply a resin solution or a resin composition to a solution glass fiber, and then the glass fiber coated with the resin solution or the resin composition solution is dried. In addition, the coating of glass fiber with organic matter can also be carried out in the following manner: the glass fiber of the present embodiment in a fabric form is immersed in a treatment agent composition solution, and then the glass fiber to which the treatment agent composition is applied is dried.

[0074] Here, examples of the silane coupling agent include aminosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, and (meth)acrylic silane. In the present embodiment, the above silane coupling agents may be used alone or in combination of two or more.

[0075] Examples of the aminosilane include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N′-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-anilinopropyltrimethoxysilane.

[0076] Examples of the chlorosilane include γ-chloropropyltrimethoxysilane and the like.

[0077] Examples of epoxysilane include β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane.

[0078] Examples of the mercaptosilane include γ-mercaptotrimethoxysilane and the like.

[0079] Examples of the vinyl silane include vinyltrimethoxysilane and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane.

[0080] Examples of the (meth)acrylic silane include γ-methacryloxypropyltrimethoxysilane and the like.

[0081] As lubricants, there can be mentioned: modified silicone oil, animal oil and hydrogenated additives thereof, vegetable oil and hydrogenated additives thereof, animal wax, vegetable wax, mineral wax, condensation products of higher saturated fatty acids and higher saturated alcohols, polyethylene imine, polyalkyl polyamine alkyl linolenic acid derivatives, fatty acid amides, quaternary ammonium salts. In the present embodiment, the above lubricants can be used alone, or two or more of the above lubricants can be used in combination.

[0082] Examples of animal oils include beef tallow and the like.

[0083] Examples of the vegetable oil include soybean oil, coconut oil, rapeseed oil, palm oil, and castor oil.

[0084] Examples of the animal wax include beeswax and lanolin.

[0085] Examples of the vegetable wax include candelilla wax and carnauba wax.

[0086] Examples of the mineral wax include paraffin wax and montan wax.

[0087] Examples of the condensate of a higher saturated fatty acid and a higher saturated alcohol include stearic acid esters such as lauryl stearic acid.

[0088] Examples of fatty acid amides include dehydration condensates of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentamine, and fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid.

[0089] Examples of the quaternary ammonium salt include alkyltrimethylammonium salts such as lauryltrimethylammonium chloride.

[0090] Examples of the surfactant include nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants. In the present embodiment, the above surfactants may be used alone or in combination of two or more.

[0091] Examples of the nonionic surfactant include ethylene oxide propylene oxide alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene-block copolymers, alkyl polyoxyethylene-polyoxypropylene-block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, ethylene oxide propylene oxide alkyl ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerol fatty acid esters, pentaerythritol fatty acid esters, sorbitol fatty acid esters, sorbitol fatty acid esters, sucrose fatty acid esters, polyhydric alcohol alkyl ethers, fatty acid alkanolamides, acetylene glycols, ethylene oxide adducts of acetylene glycols, and ethylene oxide adducts of acetylene alcohols.

[0092] Examples of cationic surfactants include alkyl dimethyl benzyl ammonium chloride, alkyl trimethyl ammonium chloride, alkyl dimethyl ethyl ammonium ethyl sulfate, higher alkyl amine salts, ethylene oxide adducts of higher alkyl amines, condensates of higher fatty acids and polyalkylene polyamines, salts of esters of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline type cationic surfactants, and alkyl pyridinium salts. Examples of higher alkyl amine salts include acetates and hydrochlorides.

[0093] Examples of anionic surfactants include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphates of higher alcohol ethylene oxide adducts.

[0094] Examples of amphoteric surfactants include amino acid type amphoteric surfactants, betaine type amphoteric surfactants, and imidazoline type amphoteric surfactants. Examples of amino acid type amphoteric surfactants include alkyl aminopropionic acid alkali metal salts, and examples of betaine type amphoteric surfactants include alkyl dimethyl betaine.

[0095] The glass fiber fabric of the present embodiment includes the glass fiber of the present embodiment described above. Specifically, the glass fiber fabric of the present embodiment can be obtained by weaving the glass fiber of the present embodiment described above as at least a part of the warp or weft using a loom known to itself. As the loom described above, for example, jet looms such as air jet looms or water jet looms, shuttle looms, rapier looms, etc. can be cited. In addition, as the weaving method using the loom described above, for example, plain weave, satin weave, basket weave, twill weave, etc. can be cited, and from the viewpoint of manufacturing efficiency, plain weave is preferred. The glass fiber fabric of the present embodiment preferably uses the glass fiber described above in the present embodiment as the warp and weft.

[0096] In the glass fiber fabric of this embodiment, the above-mentioned glass fiber of this embodiment is formed by bundling 35 to 400 glass filaments with a filament diameter range of 3.0 to 9.0 μm, with a twist range of 0 to 1.0 times / 25 mm, and a mass preferably ranges from 0.9 to 69.0 tex (g / 1000 m).

[0097] In the glass fiber fabric of the present embodiment, when the glass fiber of the present embodiment is used as a warp or a weft, the warp weaving density is preferably in the range of 40 to 120 yarns / 25 mm, and the weft weaving density is preferably in the range of 40 to 120 yarns / 25 mm.

[0098] The glass fiber fabric of the present embodiment may be subjected to deoiling treatment, surface treatment, and fiber opening treatment after weaving.

[0099] As an example of the deoiling treatment, there can be mentioned a treatment in which the glass fiber fabric is placed in a heating furnace at an atmospheric temperature in the range of 350 to 400° C. for 40 to 80 hours to heat and decompose organic matter adhering to the glass fiber.

[0100] As an example of surface treatment, the following treatment can be cited: immersing the glass fiber fabric in a solution containing the above-mentioned silane coupling agent or containing the above-mentioned silane coupling agent and the above-mentioned surfactant, after squeezing out excess water, heating and drying at a temperature in the range of 80° C. to 180° C. for a time range of 1 to 30 minutes.

[0101] Examples of fiber opening treatments include the following: while applying a tension in the range of 30 to 200 N to the warp yarns of the glass fiber fabric, fiber opening with surface pressure using water flow pressure and high-frequency vibration using liquid as a medium, fiber opening using roller pressure, etc. to increase the width of the warp yarns and weft yarns.

[0102] The glass fiber fabric of this embodiment preferably has a mass range of 7.0 to 190.0 g / m 2 The quality and thickness range are 8.0~200.0μm.

[0103] The glass fiber woven fabric of the present embodiment preferably has a warp width in the range of 110 to 600 μm, and preferably has a weft width in the range of 110 to 600 μm.

[0104] The glass fiber fabric of this embodiment may include a surface treatment layer containing the above-mentioned silane coupling agent or containing the above-mentioned silane coupling agent and the above-mentioned surfactant. When the glass fiber fabric of this embodiment includes the above-mentioned surface treatment layer, the surface treatment layer may have a mass range of 0.03 to 1.50 mass % relative to the total amount of the glass fiber fabric including the surface treatment layer.

[0105] The glass fiber reinforced resin composition of the present embodiment contains the aforementioned glass fiber of the present embodiment. Specifically, the glass fiber reinforced resin composition of the present embodiment is a glass fiber reinforced resin composition containing a thermoplastic resin or a thermosetting resin, glass fiber and other additives, wherein the glass fiber reinforced resin composition contains 10 to 90% by mass of glass fiber relative to the total amount of the glass fiber reinforced resin composition. In addition, the glass fiber reinforced resin composition of the present embodiment contains 90 to 10% by mass of resin relative to the total amount of the glass fiber reinforced resin composition, and contains other additives in the range of 0 to 40% by mass.

[0106] Here, examples of thermoplastic resins include polyethylene, polypropylene, polystyrene, styrene / maleic anhydride resin, styrene / maleimide resin, polyacrylonitrile, acrylonitrile / styrene (AS) resin, acrylonitrile / butadiene / styrene (ABS) resin, chlorine-modified polyethylene / acrylonitrile / styrene (ACS) resin, acrylonitrile / ethylene / styrene (AES) resin, acrylonitrile / styrene / methyl acrylate (ASA) resin, styrene / acrylonitrile (SAN) resin, methacrylic resin, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyamide, polyacetal, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyphenylene terephthalate (PBT), polybutyl ... Propylene glycol dicarboxylate (PTT), polycarbonate, polyarylene sulfide, polyethersulfone (PES), polyphenylene sulfone (PPSU), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyaryletherketone, liquid crystal polymer (LCP), fluororesin, polyetherimide (PEI), polyarylate (PAR), polysulfone (PSF), polyamideimide (PAI), polyaminobismaleimide (PABM), thermoplastic polyimide (TPI), polyethylene naphthalate (PEN), ethylene / vinyl acetate (EVA) resin, ionomer (IO) resin, polybutadiene, styrene / butadiene resin, polybutene, polymethylpentene, olefin / vinyl alcohol resin, cycloolefin resin, cellulose resin, polylactic acid, etc.

[0107] Examples of polyethylene include high-density polyethylene (HDPE), medium-density polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene.

[0108] Examples of polypropylene include isotactic polypropylene, atactic polypropylene, syndiotactic polypropylene, and mixtures thereof.

[0109] Examples of polystyrene include general-purpose polystyrene (GPPS) which is atactic polystyrene having an atactic structure, high impact polystyrene (HIPS) obtained by adding a rubber component to GPPS, and syndiotactic polystyrene having a syndiotactic structure.

[0110] Examples of the methacrylic resin include polymers obtained by polymerizing one methacrylic acid resin selected from the group consisting of acrylic acid, methacrylic acid, styrene, methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, and fatty acid vinyl esters, or polymers obtained by copolymerizing two or more of the above methacrylic resins.

[0111] Examples of polyvinyl chloride include homopolymers of vinyl chloride polymerized by conventionally known methods such as emulsion polymerization, suspension polymerization, microsuspension polymerization, and bulk polymerization, copolymers thereof with monomers copolymerizable with vinyl chloride monomers, and graft copolymers thereof in which vinyl chloride monomers are graft-polymerized onto polymers.

[0112] Examples of polyamides include polycaprolactam (nylon 6), polyhexamethylene adipamide (nylon 66), polybutylene adipamide (nylon 46), polybutylene sebacate (nylon 410), polypentamethylene adipamide (nylon 56), polysebamide (nylon 510), polyhexamethylene sebacate (nylon 610), polyhexamethylene dodecanoamide (nylon 612), polydecamethylene adipamide (nylon 106), polydecanediamide (nylon 410), polypentamethylene adipamide (nylon 56), polysebamide (nylon 510), polyhexamethylene sebacate (nylon 610), polydodecanediamide (nylon 612), polydecamethylene adipamide (nylon 106), polydecanediamide (nylon 410). (Nylon 1010), polydodecane diamide (Nylon 1012), polyundecanamide (Nylon 11), polyhexamethylene adipamide (Nylon 116), polydodecane amide (Nylon 12), polyxylene hexamethylenediamine (Nylon XD6), polyxylene sebacic acid amide (Nylon XD10), polymethylene adipamide (Nylon MXD6), polymethylene adipamide (Nylon PXD6), polyterephthalamide (Nylon 4T), poly Pentamethylene terephthalamide (nylon 5T), polyhexamethylene terephthalamide (nylon 6T), polyhexamethylene isophthalamide (nylon 6I), polynonane terephthalamide (nylon 9T), polydecane terephthalamide (nylon 10T), polyundemethylene terephthalamide (nylon 11T), polydodecamethylene terephthalamide (nylon 12T), polytetramethylene phthalamide (nylon 4I), polybis(3-methyl-4-aminohexamethylene terephthalamide) One of the components selected from the group consisting of poly(3-methyl-4-aminohexyl)methane terephthalamide (nylon PACMT), poly(3-methyl-4-aminohexyl)methane isophthalamide (nylon PACMI), poly(3-methyl-4-aminohexyl)methane dodecanamide (nylon PACM12), poly(3-methyl-4-aminohexyl)methane tetradecamide (nylon PACM14), or a copolymer of two or more of the components, or a mixture of these components.

[0113] Examples of polyacetal include homopolymers having oxymethylene units as main repeating units and copolymers mainly containing oxymethylene units and having oxyalkylene units having 2 to 8 adjacent carbon atoms in the main chain.

[0114] Examples of polyethylene terephthalate include polymers obtained by polycondensation of terephthalic acid or a derivative thereof and ethylene glycol.

[0115] Examples of polybutylene terephthalate include polymers obtained by polycondensation of terephthalic acid or a derivative thereof and 1,4-butanediol.

[0116] Examples of polytrimethylene terephthalate include polymers obtained by polycondensation of terephthalic acid or a derivative thereof and 1,3-propylene glycol.

[0117] Examples of polycarbonates include polymers obtained by an ester exchange method in which a dihydroxydiaryl compound is reacted with a carbonate such as diphenyl carbonate in a molten state, and polymers obtained by a phosgene method in which a dihydroxydiaryl compound is reacted with phosgene.

[0118] Examples of polyarylene sulfide include linear polyphenylene sulfide, cross-linked polyphenylene sulfide having a high molecular weight by a curing reaction after polymerization, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone.

[0119] Examples of the polyphenylene ether include poly(2,3-dimethyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-chloromethyl-1,4-phenylene ether), poly(2-methyl-6-hydroxyethyl-1,4-phenylene ether), poly(2-methyl-6-n-butyl-1,4-phenylene ether), poly(2-ethyl-6-isopropyl-1,4-phenylene ether), poly(2-ethyl-6-n-propyl-1,4-phenylene ether), poly(2,3,6-trimethyl-1,4-phenylene ether), poly[2-(4'-methylphenyl)-1,4-phenylene ether], poly(2-bromo-6-phenyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2-phenyl- 4-phenylene ether), poly(2-chloro-1,4-phenylene ether), poly(2-methyl-1,4-phenylene ether), poly(2-chloro-6-ethyl-1,4-phenylene ether), poly(2-chloro-6-bromo-1,4-phenylene ether), poly(2,6-di-n-propyl-1,4-phenylene ether), poly(2-methyl-6-isopropyl-1,4-phenylene ether), poly(2-chloro-6-methyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2,6-dibromo-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), poly(2,6-dimethyl-1,4-phenylene ether), and the like.

[0120] Examples of modified polyphenylene ethers include polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polystyrene, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / maleic anhydride copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polyamides, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene / acrylonitrile copolymers, modified polyphenylene ethers in which functional groups such as amino groups, epoxy groups, carboxyl groups, and styryl groups are introduced into the polymer chain terminals of the above polyphenylene ethers, and modified polyphenylene ethers in which functional groups such as amino groups, epoxy groups, carboxyl groups, styryl groups, and methacryloyl groups are introduced into the polymer chain side chains of the above polyphenylene ethers.

[0121] Examples of the polyaryletherketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyetheretherketoneketone (PEEKK).

[0122] Examples of liquid crystal polymers (LCP) include (co)polymers composed of structural units of one or more components selected from the following components: aromatic hydroxycarbonyl units, aromatic dihydroxy units, aromatic dicarbonyl units, aliphatic dihydroxy units, aliphatic dicarbonyl units, etc., which are thermotropic liquid crystal polyesters.

[0123] Examples of fluororesins include polytetrafluoroethylene (PTFE), perfluoroalkoxy resin (PFA), fluorinated ethylene propylene resin (FEP), fluorinated ethylene tetrafluoroethylene resin (ETFE), polyethylene fluoride (PVF), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), ethylene / chlorotrifluoroethylene resin (ECTFE), and the like.

[0124] Examples of the ionomer (IO) resin include copolymers of olefins or styrene and unsaturated carboxylic acids, wherein a part of the carboxyl groups are neutralized with metal ions.

[0125] Examples of the olefin / vinyl alcohol resin include ethylene / vinyl alcohol copolymers, propylene / vinyl alcohol copolymers, ethylene / vinyl acetate copolymer saponified products, and propylene / vinyl acetate copolymer saponified products.

[0126] Examples of the cyclic olefin resin include monocyclic compounds such as cyclohexene, polycyclic compounds such as tetracyclic cycloolefins, and polymers of cyclic olefin monomers.

[0127] Examples of the polylactic acid include poly-L-lactic acid which is an L-form homopolymer, poly-D-lactic acid which is a D-form homopolymer, and stereocomplex polylactic acid which is a mixture thereof.

[0128] Examples of the cellulose resin include methyl cellulose, ethyl cellulose, hydroxy cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, cellulose propionate, and cellulose butyrate.

[0129] In addition, examples of the above-mentioned thermosetting resins include: unsaturated polyester resins, vinyl ester resins, epoxy (EP) resins, melamine (MF) resins, phenolic resins (PF), polyurethane resins (PU), polyisocyanates, polyisocyanurates, polyimides (PI), urea-formaldehyde (UF) resins, silicone (SI) resins, furan (FR) resins, benzoguanamine (BR) resins, alkyd resins, xylene resins, bismaleimide triazine (BT) resins, diallyl phthalate resins (PDAP), and the like.

[0130] Examples of the unsaturated polyester resin include resins obtained by esterification reaction of an aliphatic unsaturated dicarboxylic acid and an aliphatic diol.

[0131] Examples of the vinyl ester resin include divinyl ester resins and novolac-based vinyl ester resins.

[0132] Examples of epoxy resins include bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol E epoxy resins, bisphenol S epoxy resins, bisphenol M epoxy resins (4,4'-(1,3-phenylene diisopropylidene) bisphenol type epoxy resins), bisphenol P epoxy resins (4,4'-(1,4-phenylene diisopropylidene) bisphenol type epoxy resins), bisphenol Z epoxy resins (4,4'-cyclohexylene diphenol type epoxy resins), phenol novolac epoxy resins, cresol novolac epoxy resins, and tetraphenol ethane type epoxy resins. Novolac type epoxy resin, novolac type epoxy resin having a condensed aromatic hydrocarbon structure, biphenyl type epoxy resin, xylene type epoxy resin or phenyl aralkyl type epoxy resin and other aralkyl type epoxy resins, naphthylene ether type epoxy resin, naphthol type epoxy resin, naphthodiol type epoxy resin, bifunctional or tetrafunctional epoxy type naphthalene resin, binaphthyl type epoxy resin, naphthalene aralkyl type epoxy resin, anthracene type epoxy resin, phenoxy type epoxy resin, dicyclopentadiene type epoxy resin, norbornene type epoxy resin, adamantane type epoxy resin, fluorene type epoxy resin, etc.

[0133] Examples of the melamine resin include polymers formed by polycondensation of melamine (2,4,6-triamino-1,3,5-triazine) and formaldehyde.

[0134] Examples of phenolic resins include novolac-type phenolic resins such as phenol novolac resins, cresol novolac resins, and bisphenol A novolac resins, resol-type phenolic resins such as methylol resol resins and dimethylene ether resol resins, and aryl alkylene phenolic resins, or a combination of two or more of these resins.

[0135] Examples of the urea-formaldehyde resin include resins obtained by condensation of urea and formaldehyde.

[0136] The above-mentioned thermoplastic resin or the above-mentioned thermosetting resin may be used alone or in combination of two or more kinds of resins.

[0137] The glass fiber reinforced resin composition of the present embodiment is used for applications requiring low dielectric properties, and therefore epoxy resin, modified polyphenylene ether, polybutylene terephthalate, polypropylene, fluororesin, and liquid crystal polymer (LCP) are preferred as the resin.

[0138] Other additives include reinforcing fibers other than glass fibers, fillers other than glass fibers, flame retardants, ultraviolet absorbers, heat stabilizers, antioxidants, antistatic agents, flow improvers, antiblocking agents, lubricants, nucleating agents, antibacterial agents, pigments, and the like.

[0139] Examples of reinforcing fibers other than glass fibers include carbon fibers and metal fibers.

[0140] Examples of fillers other than glass fibers include glass powder, talc, and mica.

[0141] The glass fiber reinforced resin composition of the present embodiment may be a prepreg obtained by impregnating the glass fiber woven fabric of the present embodiment with the resin by a method known per se and semi-curing the impregnated glass fiber woven fabric.

[0142] The glass fiber reinforced resin composition of the present embodiment can be molded by known molding methods such as injection molding, injection compression molding, two-color molding, hollow molding, foam molding (including supercritical fluid), insert molding, in-mold coating molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, stamping, melting, hand lay-up, spraying, resin transfer molding, sheet molding, bulk molding, pultrusion, and filament winding to obtain various glass fiber reinforced resin molded products. In addition, by curing the above-mentioned prepreg, a glass fiber reinforced resin molded product can also be obtained.

[0143] Examples of uses of such molded articles include electronic equipment housings, electronic parts, vehicle exterior parts, vehicle interior parts, vehicle engine peripheral parts, muffler-related parts, and high-pressure tanks.

[0144] Examples of electronic components include printed wiring boards and the like.

[0145] Examples of vehicle exterior parts include bumpers, fenders, hoods, air dams, wheel housings, and the like.

[0146] Examples of vehicle interior parts include door trims and ceiling materials.

[0147] Examples of vehicle engine peripheral parts include an oil pan, an engine cover, an intake manifold, an exhaust manifold, and the like.

[0148] Examples of the muffler-related parts include muffler parts and the like.

[0149] It should be noted that the glass fiber of the present embodiment can be used as a reinforcing material for inorganic materials such as gypsum and cement in addition to the glass fiber reinforced resin composition of the present embodiment. For example, when used as a reinforcing material for gypsum (especially a gypsum board with a thickness of 4 to 60 mm), the gypsum contains glass fibers having a glass composition within the above range in an amount of 0.1 to 4.0 mass % relative to the total mass of the gypsum.

[0150] Next, examples of the present invention and comparative examples are shown.

[0151] Example

[0152] First, glass raw materials were mixed to obtain glass batches so that the glass compositions after melting and solidification would be the compositions of Examples 1 to 7 shown in Table 1 and Comparative Examples 1 to 6 shown in Table 2, respectively.

[0153] Next, a glass batch material corresponding to the glass composition for glass fiber of each embodiment or each comparative example was placed in a platinum crucible with a diameter of 80 mm, melted at a temperature of 1650° C. for 24 hours, and then taken out of the crucible to obtain a glass block. The obtained glass block was slowly cooled at a temperature of 580° C. for 2 hours, and the number of bubbles per gram (1 g) of glass was counted. The results are shown in Tables 1 and 2.

[0154] Next, a glass batch material corresponding to the glass composition for glass fiber of each embodiment or each comparative example was placed in a platinum crucible with a diameter of 80 mm, and the temperature was raised from room temperature to 1650°C at a heating rate of 10°C / min, and after melting at a temperature of 1650°C for 2 hours, the temperature was lowered to 1450°C at a cooling rate of 10°C / min, and the time until the number of bubbles per gram (1g) of glass was 1 or less was measured, and it was taken as the degassing process time. The degassing process time was evaluated as "◎" when the time until the number of bubbles per gram of glass was 1 or less from the time of cooling to 1450°C was less than 10 minutes, "○" when the degassing process time was less than 30 minutes, and "×" when the degassing process time was more than 30 minutes. The results are shown in Tables 1 and 2 as the degassing process time.

[0155] Next, a glass batch material corresponding to the glass composition for glass fiber of each embodiment or each comparative example is placed in a platinum crucible with a diameter of 80 mm, and the temperature is raised from room temperature to 1650°C at a heating rate of 10°C / min. After melting at 1650°C for 2 hours, the temperature is lowered to 1450°C at a cooling rate of 10°C / min, and maintained for 10 minutes, and then taken out from the crucible to obtain a homogeneous glass block. The obtained glass block is slowly cooled at a temperature of 580°C for 2 hours to obtain a test piece. The test piece is ground to make a ground test piece of 80 mm×3 mm (thickness 1 mm). Next, the obtained ground test piece is absolutely dried and stored indoors at a temperature of 23°C and a humidity of 60% for 24 hours. Next, the dielectric constant (dielectric constant Dk) and dielectric loss tangent (dissipation factor Df) of the polished test piece obtained at 10 GHz were measured using a dielectric constant measuring device of the cavity resonator method (manufactured by AET Co., Ltd., trade name: ADMS01Oc1) in accordance with JIS C 2565:1992. It should be noted that the dielectric constant of Example 1 is 4.3 and the dielectric loss tangent is 0.0015, the dielectric constant of Examples 4 and 7 is 4.3 and the dielectric loss tangent is 0.0016, and the dielectric constant of Example 6 is 4.3 and the dielectric loss tangent is 0.0018.

[0156] [Table 1]

[0157] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 <![CDATA[SiO 2 (parts by mass)]]> 51.1 52.7 53.5 56.5 53.0 51.5 54.9 <![CDATA[B 2 O 3 (parts by mass)]]> 24.1 23.7 23.3 21.2 23.7 24.4 21.2 <![CDATA[A12O 3 (parts by mass)]]> 15.1 124 12.3 145 12.3 16.3 15.5 MgO (parts by mass) o.5 1.5 1.5 0.5 1.5 2.1 0.5 CaO (parts by mass) 3.1 5.0 4.8 2.3 5.0 1.7 2.4 SrO (parts by mass) 3.6 0.4 2.8 3.4 0.4 2.2 3.6 <![CDATA[TiO 2 (parts by mass)]]> 1.0 3.0 1.0 1.0 2.9 1.0 1.1 <![CDATA[F 2 (parts by mass)]]> 1.5 1.3 0.8 0.6 1.2 0.8 0.8 <![CDATA[Na 2 O (parts by mass)]]> 0.0 0.0 0.0 00 00 00 0.0 <![CDATA[Fe 2 O 3 (parts by mass)]]> 0.0 0.0 00 0.0 0.0 0.0 0.0 Total (mass %) 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[Nb 2 O 5 (Mass %)]]> 0.0013 0.0014 0.0029 0.0254 0.0028 0.0426 0.0005 <![CDATA[SO 3 (Mass %)]]> 0.0052 0.0047 0.0062 0.0056 0.0048 0.0039 0.0042 <![CDATA[SO 3 / Nb 1 O 5 ]]> 4.00 3.36 2.14 0.22 1.71 0.09 8.40 Number of bubbles (pieces / g) 0 0 0 0 0 0 0 Degassing process time ◎ ◎ ◎ ◎ ◎ ○ ○

[0158] [Table 2]

[0159] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 <![CDATA[SiO 2 (parts by mass)]]> 54.9 56.5 56.4 52.4 51.1 51.7 <![CDATA[B 2 O 3 (parts by mass)]]> 21.2 21.2 19.3 24.1 24.1 24.4 <![CDATA[Al 2 O 3 (parts by mass)]]> 15.5 14.5 16.5 12.4 15.1 16.3 MgO (parts by mass) 0.5 0.5 0.5 1.5 0.5 2.1 CaO (parts by mass) 2.4 23 2.3 4.9 3.1 1.7 SrO (parts by mass) 3.6 3.4 3.2 0.4 3.5 2.0 <![CDATA[TiO 2 (parts by mass)]]> 1.1 1.0 1.0 2.9 1.0 1.0 <![CDATA[F 2 (parts by mass)]]> 0.8 0.6 0.8 1.4 1.6 0.8 <![CDATA[Na 2 O (parts by mass)]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Fe 2 O 3 (parts by mass)]]> 0.0 0.0 0.0 0.0 0.0 0.0 Total (mass parts) 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[Nb 2 O 5 (Mass %)]]> 0.0001 00741 0.1648 0.2058 0.0001 0.3096 <![CDATA[SO 3 (Mass %)]]> 0.0039 0.0031 0.0036 0.0028 00038 0.0034 <![CDATA[SO 3 / Nb 2 O 5 ]]> 39.00 0.04 0.02 0.01 38.00 0.01 Number of bubbles (pieces / g) 0 0 0 0 0 0 Degassing process time × × × × × ×

[0160] It is obvious from Table 1 that according to the glass batch material corresponding to the glass composition for glass fiber of Examples 1 to 7, the number of bubbles after melting at a temperature of 1650°C for 24 hours is zero, and the degassing process time is less than 10 minutes or less than 30 minutes, which can shorten the time required for the degassing process.

[0161] On the other hand, it is obvious from Table 2 that 3 The content relative to Nb 2 O 5 The content ratio (SO 3 / Nb 2 O 5 ) value exceeds 13.70, or the glass batch material corresponding to the glass composition for glass fiber of Comparative Examples 1 and 5, or SO 3 The content relative to Nb 2 O 5 The content ratio (SO 3 / Nb 2 O 5 ) value of less than 0.07, the glass batch material corresponding to the glass composition for glass fiber of Comparative Examples 2 to 4, 6 has zero bubble number after being melted at a temperature of 1650°C for 24 hours, but the degassing process time is more than 30 minutes, and the time required for the degassing process cannot be shortened.

Claims

1. A glass composition for glass fiber, characterized in that: The glass composition for glass fiber contains 0.0001 to 0.3500 mass % of Nb2O5 and 0.0010 to 0.0100 mass % of SO3, relative to the total amount of the glass composition for glass fiber. When the remainder after removing SO3 and Nb2O5 from the total amount of the glass composition for glass fiber is set to 100 parts by mass, the glass composition for glass fiber contains SiO2 in a range of 48.0 to 60.0 parts by mass, B2O3 in a range of 18.4 to 27.0 parts by mass, Al2O3 in a range of 10.8 to 17.0 parts by mass, MgO in a range of 0 to 2.5 parts by mass, CaO in a range of 0 to 6.0 parts by mass, SrO in a range of 0 to 4.5 parts by mass, TiO2 in a range of 0.5 to 3.5 parts by mass, and F2 and Cl2 in a range of 0 to 2.5 parts by mass in total, The ratio of the content of SO 3 to the content of Nb 2 O 5 , that is, the value of SO 3 / Nb 2 O 5 is in the range of 0.07 to 13.

70.

2. The glass composition for glass fiber according to claim 1, characterized in that: The ratio of the content of SO 3 to the content of Nb 2 O 5 , that is, the value of SO 3 / Nb 2 O 5 is in the range of 0.16 to 6.

20.

3. A glass fiber, characterized in that: The invention comprises glass filaments formed from the glass composition for glass fibers according to claim 1.

4. A glass fiber fabric, characterized in that: The glass fiber according to claim 3 is included.

5. A glass fiber reinforced resin composition, characterized in that: The glass fiber according to claim 3 is included.

Citation Information

Patent Citations

  • Production of globular metal powder

    JP1989068409A

  • Mobile phone cover plate glass capable of meeting requirements of 5G communication and 3D compression molding and process method

    CN109626816A

  • Glass composition for glass fiber, glass fiber, and glass fiber-reinforced resin composition using same

    CN110719897A